Electoral Reforms and the Administration of the 2015 General Elections in Nigeria. Issue 3 (3rd July 2019) - Basiru, Adeniyi; Adesina, Kola
ABSTRACT: Since the return of Nigeria to civil democracy in 1999, elections and their administration by the electoral body, like they were in the previous defunct republics, have been rather problematic to the effect that many observers have even doubted whether electoral democracy could fit in into the country's social milieu. However, in recent times, following the controversial and widely condemned elections of 2003 and 2007, a series of electoral reforms have been initiated to improve the quality of elections in the country. This article, adopting descriptive and historical methodology, examines how the series of reforms initiated by the Electoral Management Body (EMB), the Independent National Electoral Commission (INEC) before the 2015 general elections impinged on the overall outcome of the exercises. The article notes that there were tremendous improvements in the administration of the 2015 General elections by INEC. It argues that the improved electoral administration of the 2015 General elections may be connected with the reforms initiated by the elections body prior to the 2015 elections. It concludes that, even though, INEC may have fared better in comparison with how it handled similar endeavors in the past, yet more works still need to be done in order to have even better outcomes in the 2019 round of elections.